Crohn’s Disease – Epidemiology, Clinical Presentation and Treatment Possibilities - Kutnik, Kacper; Woźnica, Weronika; Dąbrowska, Julia; Lambach, Jakub; Mazurek, Katarzyna; Gęborys, Anna; Wojcieszak, Maja; Matuszewska, Julia; Miazga, Dominika; Maziarczyk, Alicja (Quality in Sport, 2026)
Introduction. Crohn’s disease is a chronic, relapsing–remitting inflammatory disorder of the gastrointestinal tract. Once concentrated primarily in high-income regions, Crohn’s disease has now become a global condition. Advances in understanding immune and stromal cell populations, their interactions, and the cytokine and chemokine networks that drive pathogenesis and rapid technological progress have greatly broadened therapeutic options. Currently treatment strategies aim not only to induce and maintain deep, durable remission, but also to prevent complications and slow or stop the progressive nature of the disease. Aim. The aim of this review is to summarize current evidence of epidemiology, pathophysiology, diagnosis, and treatment options in Crohn’s disease. Material and methods. This research involves a review of literature found in PubMed, Google Scholar, electronic databases, and books using key words combinations such as “Crohn’s disease”, “symptoms”, “epidemiology”, “and”, “treatment”, “clinical trial”, “risk factors”, “pathogenesis”, “surgery”. Conclusions. Despite advancements in Crohn’s disease treatment, recurrence rate is still at high levels resulting in the need for surgical management for the majority of patients diagnosed with Crohn’s disease. Further studies are still necessary to confirm efficacy and potential of existing treatment options and to search for new substances, which might be effective in Crohn’s disease management.